Ego In The Main Character In The Novel "Pulang" By Tere Liye - Aini, Ika Nur; Resdianto Permata Raharjo (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The purpose of this research is to explore how the main character, known as "Bujang", shows an ego-focused personality by referring to Sigmund Freud's personality theory in the novel Pulang written by Tere Liye and published by Republika in 2015. This research method involves the following steps: preparation, including reading the novel thoroughly to gain an in-depth understanding as a primary source, and reading related research as supporting data; data collection, where the researcher identifies information related to the character's personality characteristics based on Sigmund Freud's theory; and data analysis, using a psychoanalytic approach, especially personality theory according to Sigmund Freud, focusing on the ego of the main character. In data analysis, researchers highlighted the dominance of ego elements in the personality of the main character, namely Bujang. Bujang is able to control the desires of his id, so that the actions and decisions he takes are based on the reality he experiences.